Freedom from Reality : The Diabolical Character of Modern Liberty - Schindler, D. C. (Book collections on Project MUSE., 2017)
Presents a critique of the deceptive and ultimately self-subverting character of the modern notion of freedom, retrieving an alternative view through a new interpretation of the ancient tradition.